2004
DOI: 10.1002/cne.20050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen replacement therapy on cholinergic basal forebrain neurons and cortical cholinergic innervation in young and aged ovariectomized rhesus monkeys

Abstract: Estrogen modulates the function of cholinergic basal forebrain neurons in aged female rats. The present study tested the hypothesis that estrogen enhances the phenotype of cholinergic basal forebrain neurons and their cortical cholinergic innervation in young adult and aged ovariectomized rhesus monkeys. Sixteen monkeys (9 young and 7 aged) received two injections of estradiol cypionate or vehicle separated by 3 weeks. All monkeys were killed 1 day after the last injection. Quantitative immunofluorescence in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 64 publications
(65 reference statements)
6
23
0
1
Order By: Relevance
“…Estrogen treatment has been found to directly enhance the activity of the cholinergic system by some researchers (Kompoliti et al, 2004;Bora et al, 2005). In the present study, we found that the selective ER agonist liquiritigenin enhanced the activity of Chat and decreased AchE activity, thus enhancing cholinergic functioning.…”
Section: Discussionsupporting
confidence: 66%
“…Estrogen treatment has been found to directly enhance the activity of the cholinergic system by some researchers (Kompoliti et al, 2004;Bora et al, 2005). In the present study, we found that the selective ER agonist liquiritigenin enhanced the activity of Chat and decreased AchE activity, thus enhancing cholinergic functioning.…”
Section: Discussionsupporting
confidence: 66%
“…especially during middle and old age (Kompoliti et al, 2004;Hao et al, 2006;Browne et al, 2009), it is plausible that the effects of E treatment we observed on both tasks are related to mechanisms of hormonal action in this region.…”
Section: Discussionmentioning
confidence: 74%
“…The nonhuman primate (NHP) is an attractive and highly translational alternative model (Lacreuse et al, 2015), being a long-lived, close genetic relative, with a complex brain and cognitive ability (Kohama et al, 2012). Furthermore, the reproductive physiology of female NHPs is very similar to that of women, showing characteristic monthly menstrual cycles (Jewitt and Dukelow, 1972;Knobil, 1974;Goodman et al, 1977), cycle irregularity during perimenopause Downs and Urbanski, 2006), and cessation of cyclicity and ovarian estrogen production after menopause (Johnson and Kapsalis, 1995;Walker, 1995;Downs and Urbanski, 2006). Additionally, there are significant anatomical differences that exist between the frontal lobes of primates and rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all layer III pyramidal neurons in area 46 participate in corticocortical circuitry and these neurons are vulnerable to aging (Hof and Morrison, 2004). Cholinergic and monoaminergic projections to monkey prefrontal cortex are also vulnerable to aging (Wenk et al, 1989;Arnsten, 1999) and responsive to estrogen, particularly in the supragranular layers Kohama, 1998, 1999;Kompoliti et al, 2004;Tinkler et al, 2004), the layers that contain most of the dendritic arbor of our target neurons. Thus, estrogen treatment in aged monkeys potentially impacts key corticocortically projecting neurons, as well as the cholinergic and monoaminergic circuits that modulate these circuits.…”
Section: Discussionmentioning
confidence: 99%